Advances in Condensed-Matter and Materials Physics - Rudimentary Research to Topical Technology 2020
DOI: 10.5772/intechopen.90042
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in Two-Dimensional Materials

Abstract: Because of the reduced dielectric screening and enhanced Coulomb interactions, two-dimensional (2D) materials like phosphorene and transition metal dichalcogenides (TMDs) exhibit strong excitonic effects, resulting in fascinating many-particle phenomena covering both intralayer and interlayer excitons. Their intrinsic bandgaps and strong excitonic emissions allow the possibility to tune the inherent optical, electrical, and optoelectronic properties of 2D materials via a variety of external stimuli, making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 158 publications
(195 reference statements)
0
11
0
Order By: Relevance
“…The Ti ions attracted around the oxygen vacancies in TiO 6 octahedral forms potential minima which localize electrons and holes to form self-trapped excitons (STE). [29][30][31] We found that the time-resolved PL at 530 nm (2.34 eV) peak is best fitted by the stretched biexponential decay model while time-resolved PL at 690 nm (1.8 eV) peak could be fitted well by simple biexponential decay model as shown in Figure S6 in the Supporting Information. This indicates that the 2.34 eV luminescence is excited from electron-hole pair excitonic state while 1.8 eV luminescence could possibly be due to the Ti vacancy defect states.…”
Section: Resultsmentioning
confidence: 80%
“…The Ti ions attracted around the oxygen vacancies in TiO 6 octahedral forms potential minima which localize electrons and holes to form self-trapped excitons (STE). [29][30][31] We found that the time-resolved PL at 530 nm (2.34 eV) peak is best fitted by the stretched biexponential decay model while time-resolved PL at 690 nm (1.8 eV) peak could be fitted well by simple biexponential decay model as shown in Figure S6 in the Supporting Information. This indicates that the 2.34 eV luminescence is excited from electron-hole pair excitonic state while 1.8 eV luminescence could possibly be due to the Ti vacancy defect states.…”
Section: Resultsmentioning
confidence: 80%
“…It should be noted that the role of various indicated factors remains unclear at length and is a subject of intense researches (see, e.g., works [16][17][18] and references therein). In any case, a reduction of the dielectric screening and an enhancement of the Coulomb interaction lead to intense exciton and multiparticle effects in 2D systems.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicate that the sharp α peak at around 1 eV observed in optical experiments [2,3,11] has either an excitonic nature, or it is related to defects/impurities, or a combination thereof. Because α−RuCl 3 is a quasi-2D material, this is not surprising since very large excitonic binding energies of that order are observed in other 2D materials [56,57]. Indeed, recent time-resolved two-photon PE spectroscopy experiments indicate that abovementioned ∼ 1 eV gap is excitonic [54].…”
Section: G Band Gapsmentioning
confidence: 91%